2015
DOI: 10.1124/jpet.115.227223
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Pharmacokinetic/Pharmacodynamic Model of Factor D Inhibition in Cynomolgus Monkeys by Lampalizumab for the Treatment of Geographic Atrophy

Abstract: Lampalizumab is an antigen-binding fragment of a humanized monoclonal antibody against complement factor D (CFD), a ratelimiting enzyme in the activation and amplification of the alternative complement pathway (ACP), which is in phase III clinical trials for the treatment of geographic atrophy. Understanding of the pharmacokinetics, pharmacodynamics, and biodistribution of lampalizumab following intravitreal administration in the ocular compartments and systemic circulation is limited but crucial for selecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 33 publications
1
27
1
Order By: Relevance
“…93,96 Inhibiting CFD decreases, but does not eliminate, classical and lectin-activated complement initiation. 68,69 Intravitreal clinically relevant doses were demonstrated to have minimal systemic inhibition of the alternative complement pathway in pharmacokinetic studies in monkeys 148,149 and in subjects participating in the Phase 1 and Phase 2 lampalizumab trials (NCT00973011; NCT01229215). 150,151 The low levels of lampalizumab in systemic circulation resulting from intravitreal administration are not expected to affect systemic alternative complement pathway activity.…”
Section: Clinical Development Of Potential Pharmacotherapiesmentioning
confidence: 99%
“…93,96 Inhibiting CFD decreases, but does not eliminate, classical and lectin-activated complement initiation. 68,69 Intravitreal clinically relevant doses were demonstrated to have minimal systemic inhibition of the alternative complement pathway in pharmacokinetic studies in monkeys 148,149 and in subjects participating in the Phase 1 and Phase 2 lampalizumab trials (NCT00973011; NCT01229215). 150,151 The low levels of lampalizumab in systemic circulation resulting from intravitreal administration are not expected to affect systemic alternative complement pathway activity.…”
Section: Clinical Development Of Potential Pharmacotherapiesmentioning
confidence: 99%
“…Those differences are acceptable to have some idea to predict about the pharmacokinetic profile of any drugs. Le et al has also investigated the lampalizumab elimination following the intravitreal injection (51). The slow ocular elimination was observed compared to systemic elimination.…”
Section: Ocular Pharmacokineticsmentioning
confidence: 99%
“…Pharmacokinetic/pharmacodynamics (PK/PD) model of Factor D inhibition in monkeys by lampalizumab for the treatment of geographic atrophy was developed by Le et al In addition, intravitreal administration of lampalizumab showed therapeutic levels at the target site while minimizing systemic drug exposure to patient (51). Intravitreal injection of lampalizumab resulted in slow ocular elimination compared to systemic elimination (51).…”
Section: Ocular Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitreous humor had a maximum concentration of 169 μ g/ml at 6 hours in monkeys relative to 162 μ g/ml at 24 hours in rabbit [71,76]. Lampalizumab elimination following an intravitreal injection in cynomolgus monkeys indicated slower ocular elimination with a T 1/2 approximately 3 days compared to systemic elimination with T 1/2 of 0.8 hours [77]. Drolet DW et al have studied the pharmacokinetic and safety profile of an anti-vascular endothelial growth factor aptamer (NX1838) in rhesus monkeys [78].…”
Section: Ocular Pharmacokineticsmentioning
confidence: 99%